Improving emergency obstetric referral systems in low and middle income countries: a qualitative study in a tertiary health facility in Ghana - Anita Anima Daniels; Aaron Abuosi (BMC, 2020)
Abstract Background Timely access to emergency obstetric care is crucial in preventing mortalities associated with pregnancy and childbirth. The referral of patients from lower levels of care to higher levels has been identified as an integral component of the health care delivery system in Ghana. To this effect, in 2012, the National Referral Policy and Guidelines was developed by the Ministry of Health (MOH) to help improve standard procedures and reduce delays which affect access to emergency care. Nonetheless, ensuring timely access to care during referral of obstetric emergencies has been problematic. The study aimed to identify barriers associated with the referral of emergency obstetric cases to the leading national referral centre. It specifically examines the lived experiences of patients, healthcare providers and relatives of patients on the referral system. Methods Korle Bu Teaching Hospital, Accra was used as a case study in 2016.The qualitative method was used and in-depth interviews were conducted with 89 respondents: healthcare providers [n = 34];patients [n = 31] and relatives of patients [n = 24] using semi-structured interview guides. Purposive sampling techniques were used in selecting healthcare providers and patients and convenience sampling techniques were used in selecting relatives of patients. Results The study identified a range of barriers encountered in the referral process and broadly fall under the major themes: referral transportation system, referrer-receiver communication barriers, inadequate infrastructure and supplies and insufficient health personnel. Some highlights of the problem included inadequate use of ambulance services, poor management of patients during transit, lack of professional escort, unannounced emergency referrals, lack of adequate information and feedback and limited supply of beds, drugs and blood. These findings have implications on type II and III of the three delays model. Conclusions Initiatives to improve the transportation system for the referral of obstetric emergencies are vital in ensuring patients' safety during transfer. Communication between referring and receiving facilities should be enhanced. A strong collaboration is needed between teaching hospitals and other stakeholders in the referral chain to foster good referral practices and healthcare delivery. Concurrently, supply side barriers at referred facilities including ensuring sufficient provision for bed, blood, drugs, and personnel must be addressed.